(untitled) (Colloquium Agrariae. ISSN: 1809-8215, 2019)
Aimed to evaluate the physiological quality of seeds of crambe treated with fertilizer-based zinc and molybdenum. The experiment was conducted at the Laboratory of Seed Analysis Unimontes. The experimental design was completely randomized, with four replications. The treatments tested consisted of five doses of commercial fertilizer composed of zinc (35%) and molybdenum (3.5%), applied to seeds at concentrations of 0; 3.3; 6.7; 10:13 fertilizer ml-1 to 0.5 kg of seed. The seed quality was assessed using the following tests: germination, first count of germination, seedling emergence and length seedlings. With increasing doses of commercial fertilizer composed of zinc and molybdenum, a reduction in germination and vigor of crambe. The physiological quality of seeds of crambe is negatively influenced by increasing doses of molybdenum.